Exploitation des ressources naturelles dans l’Arctique : une évolution contrastée dans les soubresauts du marché mondial. - Pic, Pauline; Lasserre, Frédéric (Conseil québécois d’Études géopolitiques, 2021)
Arctic mineral resources have been the subject of significant media attention since the advent of narratives on melting sea ice, at the turn of the 21st century, and the episode of the planting of the Russian flag at the North Pole in 2007, an episode that fueled the idea of a race to appropriate maritime spaces and seabed resources. Carried by the high world prices that prevailed just before the 2009 financial crisis, major exploration campaigns were launched, while the States nurtured ambitious policies to develop these resources. The fall in prices following the financial crisis, then the slowdown in Chinese growth (2015), the boom in energy transition policies among Westerners from 2018, then the price war between oil producers in a context of the covid-19 pandemic (2020), have completed the pulling down of prices for many commodities. The price of certain resources remains relatively high because their use contributes to the energy transition, for the manufacture of wind turbine components, electric cars, electronic components for optimizing energy efficiency: For most other resources, it is a mixed picture that characterizes their exploitation in the Arctic. What are the trajectories of extractive mining and hydrocarbon activities, depending on the region? Far from being a rapid expansion, this sector is in fact experiencing a development constrained by factors linked to the world market for natural resources Les ressources minérales de l’Arctique sont l’objet d’une forte attention médiatique depuis l’avènement des discours sur la fonte de la banquise, au tournant du 21e siècle, et l’épisode du planter du drapeau russe au pôle Nord en 2007, qui a attisé l’idée d’une course à l’appropriation des espaces maritimes et des ressources des fonds marins. Portés par les cours mondiaux élevés des années précédant la crise financière de 2009, d’importantes campagnes d’exploration ont été lancées, tandis que les États nourrissaient d’ambitieuses politiques de valorisation de ces ressources. La chute des cours suite ...